The causes of the present inflation : an interdisciplinary explanation of inflation in Britain, Germany, and the United States - Tylecote, Andrew (New York : Wiley, 1981)
This book puts forward a new theory of inflation Tthat involves it in the fiercest and perhaps most complex debate in modern economics; yet it has been written in a way which should be easily understood by the layman.
"A Halsted Press book."
Includes bibliographical references (p. 221-227) and index
osc 31/5/17
Loans
Keywords: Inflation (Finance)